Analysis of Segmenting, Targeting, Positioning and Marketing Mix Strategies on The MSME Training and Coaching - Andriyanto, Irwin; Hamdi, Edi; Indradewa, Rhian; Munandar, Agus (Jurnal Ekonomika Dan Bisnis (JEBS), 2024)
This study aims to analyse the implementation and effectiveness of Segmenting, Targeting, Positioning (STP) and Marketing Mix NICE (Networking, Interaction, Common Interest and Experience) strategies at PT Indotraining Multi Solusi's MSME training and coaching institution. Using qualitative methods that include observation, document analysis and interviews with managers and participants, this study evaluates the effect of these strategies on increasing the marketing capacity of PT Indotraining Multi Solusi. The results show that effective integration of STP and Marketing Mix can significantly improve market understanding and competitive position with similar competitors.